Clinical relevance of HLA antibody monitoring after kidney transplantation - Morath, Christian; Opelz, Gerhard; Zeier, Martin; Süsal, Caner (Journal of immunology research, 2014)
In kidney transplantation, antibody-mediated allograft injury caused by donor HLA-specific antibodies (DSA) has recently been identified as one of the major causes of late graft loss. This paper gives a brief overview on the impact of DSA development on graft outcome in organ transplantation with a focus on risk factors for de novo alloantibody induction and recently published guidelines for monitoring of DSA during the posttransplant phase.
Gesehen am 19.10.2020